Interactive Geodesic Segmentation of n-Dimensional Medical Images on the Graphics Processor - Criminisi, Antonio; Sharp, Toby; Siddiqui, Khan (Radiological Society of North America (RSNA), 2009)
This paper presents a new, parallel segmentation algorithm which enables radiologists to separate a region of interest from 2D or 3D images accurately and efficiently. This, in turn, enables fast and accurate area/volume measurements as well as the extraction of statistics for the selected region. Our general purpose algorithm can be applied to any visible structure (e.g. a tumor or any structure) and it is driven by minimal and intuitive user interaction.